SCENARIO FORECAST OF THE IMPLEMENTATION OF THE DIGITAL MULTILEVEL MODEL OF TRANSPARENCY OF FINANCIAL RELATIONS - Zakharkin Oleksiі; Myroshnychenko, Iuliia; Novikov, Volodymyr (Socio-economic relations in the digital society, 2024)
The study aims to develop and evaluate scenarios for implementing a digital multi-level financial and economic relations transparency model, which covers public, corporate, and personal finances. The study aims to identify key factors affecting the level of transparency, assess the consequences of implementing the model, and develop strategic recommendations to improve the efficiency of financial resource management and strengthen trust between market participants. The study’s main results include the definition of three model development scenarios: optimistic, pessimistic, and realistic. Each scenario considers the specifics of public, corporate, and personal finance and reflects different levels of influence of key factors such as technological readiness, government support, and market participants’ adaptation to changes. The implications of each scenario were assessed, including the potential benefits, risks, and challenges associated with implementing the model at different levels of finance. The study’s main conclusions confirm that the digital multi-level model of transparency is an effective tool for increasing the transparency of financial and economic relations, reducing risks, and improving management efficiency. Implementing the model contributes to increasing trust in state institutions, improving corporate governance, and protecting the rights of consumers of financial services. Scenario forecasting makes it possible to adapt the model’s implementation strategies to the changing conditions of the external environment, which contributes to its stability and successful integration into the financial system. The study also identifies directions for further research, including assessing the impact of individual digital technologies, developing new methods for monitoring transparency, and exploring barriers and incentives for implementing the model across industries and regions.